Opening Hours of Polling Stations and Voter Turnout: Evidence from a Natural Experiment - Niklas Potrafke; Felix Rösel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Voter turnout has declined in many countries, raising the question of whether electoral institutions increase voter turnout. We exploit an electoral reform in the Austrian state of Burgenland as a natural experiment to identify the causal effect of polling station opening hours on voter turnout. The results show that a 10 percent increase in opening hours increased voter turnout by some 0.5 to 0.9 percentage points. The reform also influenced party vote shares. The vote share of the conservative party decreased in the course of the reform, while the vote shares of the other three main parties increased. Conservative voters tend to have an especially strict sense of civic duty and would have participated in the election in any event. Simulations indicate that parliamentary majorities in previous elections would have changed under extended opening hours in favor of the social democratic party. The opening hours of polling stations probably play a more important role in political strategies than recognized to date.
Keywords: D72; D02; Z18; 330; Voter turnout; party vote shares; opening hours of polling stations; causal effects; natural experiment; Austria.